2011
DOI: 10.1007/s10963-011-9053-7
|View full text |Cite
|
Sign up to set email alerts
|

Mortuary Variability and Status Differentiation in the Late Jomon of Hokkaido Based on the Analysis of Shuteibo (Communal Cemeteries)

Abstract: The shuteibo, a type of communal cemetery characterized by a circular embankment, was constructed in the latter half of the Late Jomon (c. 1520 cal BC-1250 cal BC) in Hokkaido, Japan. Shuteibo at the Kiusu, Misawa-1, Bibi-4 and Kashiwagi-B sites are key to understanding the complex hunter-gatherer societies of the Late Jomon. Elite graves inside the shuteibo and non-elite graves outside them show clear differences in terms of grave goods, red ocher and grave markers at Kiusu-4. These communal cemeteries may ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In many parts of the world, the ability of leaders, kin, and corporate groups to exert control over land, manual labor, raw materials, the production of specialty goods, and trade are seen as key components in the expansion of political and religious power (Cooper ; Higham et al. ; Sakaguchi ). A case study from Amanda Logan and colleagues () on maize in the Andes illustrates the ways in which this crop underwrote the expansion of the Incan empire.…”
Section: The Role Of the Economymentioning
confidence: 99%
“…In many parts of the world, the ability of leaders, kin, and corporate groups to exert control over land, manual labor, raw materials, the production of specialty goods, and trade are seen as key components in the expansion of political and religious power (Cooper ; Higham et al. ; Sakaguchi ). A case study from Amanda Logan and colleagues () on maize in the Andes illustrates the ways in which this crop underwrote the expansion of the Incan empire.…”
Section: The Role Of the Economymentioning
confidence: 99%
“…There is considerable evidence for trade and exchange within Japan during this period but, with some exceptions, the possibility of trading contacts with the mainland has rarely been discussed (Bausch, 2016). The specialist craft production found in the Late-Final Jōmon included ceramics, shell beads, jadeite ornaments, greenstone beads, polished stone axes, lacquerware and salt (Kinoshita, 2003;Bausch, 2004Bausch, , 2010Sakaguchi, 2011;Kawashima, 2015b;Matsumoto, 2011Matsumoto, , 2018a. The existence of very long-distance networks at this time is clear and Final Jōmon Kamegaoka pottery from the Tohoku region is found as far south as Okinawa (Shitara, 2018), some 2000 km as the crow flies, equivalent to the distance from Paris to Athens.…”
Section: Discussionmentioning
confidence: 99%
“…33-40;Kodama, 2003). Other distinctive monuments of the Late Jōmon in southwest Hokkaido are large circular embanked burials, which often have rich grave goods (Ikawa-Smith, 1992;Sakaguchi, 2011). The largest of these embanked burials, tomb 2 at the Kiusu site, has a diameter of 75 m and a height of 5 m (see Fig.…”
Section: Social Change In the Middle To Final Jōmon: Overviewmentioning
confidence: 99%
“…In Hokkaido, some researchers have concluded that the social stratification can be seen in the Late Jomon based on examinations of cemetery sites (Inui 1981;Yabuki 1985;Segawa 1983Segawa , 2007Kimura 2003;Sakaguchi 2011;Uwaya and Kimura 2016).…”
Section: Social Implications Of Specialized Fishing Strategiesmentioning
confidence: 99%